Understanding the Hadith on Killing Apostates and Its Relevance to Human Rights - Ahmad Pani; Uswatun Hasanah; Hedhri Nadhiran (Al-Shamela : Journal of Quranic and Hadith Studies, 2024)
Freedom of religion is a right guaranteed by religion, state and international law in the context of human rights. In Islam, this principle is reflected in the Qur'an which emphasizes that there is no coercion in religion. The issue then becomes when the Hadith states that an apostate must be killed as narrated by Imam Bukhari, then are these two sources of law contradictory? In this context, it is important to investigate the original meaning of the Hadith and its significance in relation to the issue of human rights that has spread throughout the world. Therefore, this study aims to analyze the understanding of the Hadith on killing apostates and its relevance to human rights. By using qualitative methods and Fazlur Rahman's hermeneutic theory approach known as double movement, this research answers the formulation of the problem: What is the understanding of the Hadith, and how is the correlation between the understanding of the Hadith and freedom of religion in the concept of human rights today? The results and conclusions show that the Hadith of killing apostates is allowed on the condition that the apostate has been fulfilled as an enemy of Islam. In other words, an apostate can be killed when he attacks and fights Islam after embracing Islam and passing the deferred period with an absolute decision to apostatize. Thus, the punishment of being killed can be enforced in accordance with the legal records applicable to the area of the apostate where the implementation is the authority of the imam or local leader.